Voltage profile improvement technique using transformer tap changer setting based on evolutionary programming (EP) optimization technique / Mohd Pahlawi Hanafi - Hanafi, Mohd Pahlawi (2004)
The voltage unstable condition was found to be caused by the stressed condition in a power system. Various technique were reported in order to improve the voltage stability condition such as reactive power dispatch, transformer tap changer setting, capacitor placement on the local bus and flexible transmission AC (FACTS) devices. This report presents the application of EP in optimizing transfom1er tap changer setting (TTCS) for voltage profile improvement. The objective is voltage profile improvement with the TTCS as the control variables. Tests have been conducted at various loading conditions in the IEEE 14 Bus Reliability Test System. Results showed that the proposed technique is able to improve the voltage profile in the system using the TTCS as the control variables. The optimized TTCS values can be utilized by the power system operators to perform voltage profile improvement schema.